Konten Bookstagram terhadap minat baca bagi followers-nya - Rinanda, Feby; Rohmaniyah (Librarium: Library and Information Science Journal, 2024)
Introduction: This research aims to determine the influence of bookstagram content on reading interest among its followers. Data Collection Methods: To measure this influence, the researchers distributed questionnaires to the samples in this study. The type of research used in this research is descriptive quantitative research. This research aims to find out the content of bookstagram, to find out the influence on bookstagram content and to find out how big the influence is. Data Analysis: Data analysis techniques in this research use descriptive analysis, normality test, linearity test, simple linear regression analysis test, correlation and determination coefficient analysis and hypothesis testing. Result and Discussion: In testing the hypothesis test, we got a tcount value of 11.254 > ttable 1.966, which means that the content of the bookstagram account has a significant effect on reading interest or in other words has a positive influence between the two variables. Conclusion: The content on the bookstagram account regarding reading interest for its followers shows that the content on the bookstagram account provides information that suits the needs of its followers with the content created by the bookstagram account having a good form of conveying information.